THE EFFECT OF THE ADEY & SHAYER MODEL ON THE ACHIEVEMENT AND REFLECTIVE THINKING OF HIGH SCHOOL - FOURTH-GRADE STUDENTS IN MATHEMATICS - Dr. Haider Abdul Kareem Mohsen Al-Zuhairy, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The. aim of the current research is to. identify (the effect of the Adey.& Shayer model on the achievement and contemplative thinking among fourth-grade students in mathematics). The research sample consisted of (62) fourth-grade students, distributed equally to two experimental and control groups of (31) students in each group. A test achievement was prepared consisting of (40) objective items of the (multiple choice) type with four alternatives. A test of contemplative thinking consisted of (30) items. The fact and reliability of both tests were verified. After the experiment was completed, the two tests were conducted to the students of the two research groups. The results showed that the experimental group. students who studied with the Adey & Shayer model outperformed the control group students who studied the traditional way in the two tests.